The relationship between daily healthy lifestyle and sports activity in pregnant women - Ibrahim M Abu Jamous; Ayman S. Mazahreh; Jebril E. Al-Awdat; Ahed H. ALmsaiden; Hussein O. Alkhozahe; Jasser H. Alananzeh; Taha M. Tarawneh; Yousef G. Malkieh (Universidad de Murcia, 2024)
The aim of this study was to assess the general health status, daily life-healthy dietary patterns, and sports activity level of pregnant women, and to explore their relationship with the body mass index (BMI) of these women. This cross-sectional study employed descriptive and analytical methods. A total of 198 pregnant women from healthcare centers in Qasabat Al-Tafila participated. A questionnaire was developed consisting of two sections: demographic information, and a second section that included 38 questions distributed across three sub-domains: (1) General Health Status, (2) Daily Life-Healthy Dietary Patterns, and (3) Sports Activity. Statistical analyses were performed using SPSS (V20). The women's general health status was rated as high (M=0.69), while both daily life-healthy dietary patterns (M=0.468) and sports activity (M=0.573) were rated as medium. The analysis showed statistically significant positive correlations between general health status, daily life-healthy dietary patterns, and sports activity with BMI (p < 0.01). Further, the results of multiple linear regression analysis indicated that these factors significantly influence BMI (p < 0.05). These findings highlight the important role of general health, daily life-healthy dietary patterns, and physical activity in shaping the BMI of pregnant women in Tafila Governorate. The study emphasizes the importance of promoting and maintaining a balanced and active lifestyle for pregnant women to optimize their health and well-being.